Facile synthesis of C6‐substituted benz[4, 5]imidazo[1, 2‐a]quinoxaline derivatives and their anticancer evaluation. Issue 7 (22nd March 2021) - Singh, Rahul; Kumar, Ravinder; Pandrala, Mallesh; Kaur, Parleen; Gupta, Saloni; Tailor, Dhanir; Malhotra, Sanjay V.; Salunke, Deepak B.
Abstract: Cancer remains a leading cause of death worldwide, resulting in continuous efforts to discover and develop highly efficacious anticancer drugs. High‐throughput screening of heterocyclic compound libraries is one of the promising approaches that provided several new lead molecules with a novel mechanism of action. On the basis of the promising anticancer potential of imidazoquinoxaline as well as the structurally similar imidazoquinoline‐derived scaffold, we prepared a set of C6‐substituted benzimidazo[1, 2‐ a ]quinoxaline derivatives via two novel synthetic routes using commercially available starting materials, with good to excellent yields and evaluated their anticancer activity against the NCI‐60 cancer cell lines. The one‐dose (10 µM) anticancer screening of the synthesized compounds in the NCI‐60 cell line panel revealed that the substituents have a significant role in the activity. In particular, the indole (7f ), imidazole (7g ),  and benzimidazole (7h ) derivatives showed significant activity against the triple‐negative breast cancer cell line, MDA‐MB‐468. The lead compounds also exhibited notable IC50 values against another breast cancer cell line, MCF‐7. Furthermore, it was observed that these compounds were relatively nontoxic to normal cell lines: HEK293 (human embryonic kidney cell line) and MCF12A (nontumorigenic human breast epithelial cell line). The IC50 values against healthy cells were at least 5‐ to 11‐fold higher, offering a new class of heterocycles that can be further developed as promising therapeutics for cancer treatment. Abstract : A series of C6‐substituted benzimidazo[1, 2‐ a ]quinoxaline derivatives was prepared via two novel synthetic routes using commercially available starting materials and their anticancer activities were evaluated against the NCI‐60 cancer cell panel. The indole (7f ), imidazole (7g ), and benzimidazole (7h ) derivatives showed significant activity against the triple‐negative breast cancer cell line, MDA‐MB‐468.